Malas Menjadi Antusias : Transformasi pengajaran Sekolah Minggu Lewat Gamifikasi - Bangun Bangun (Pusat Riset dan Inovasi Nasional, 2025)
This effort aims to improve the effectiveness of teaching in Sunday School through the application of gamification approaches as an innovative learning method. The problem faced by Sunday School teachers is the low level of participation and motivation of children in Bible study activities, which tend to be one-way, monotonous, and lack active student participation. Traditional approaches are often unable to engage children, so the learning process becomes less effective in instilling the values of faith and spirituality. Gamification—the application of game elements such as points, challenges, badges, leaderboards, and level systems in non-gaming activities—is believed to create a more fun, healthy, and motivating learning environment. This approach stimulates children's emotional and cognitive involvement in the learning process, while encouraging active participation and a sense of accomplishment. The activity was carried out through a series of training and mentoring to teachers, including understanding the basic concepts of gamification, the preparation of the design of game-based learning activities that are contextual with biblical materials, and direct application in classroom sessions. Teachers are trained to create creative challenges that encourage collaboration and problem-solving, without overriding the primary purpose of faith learning. Theoretically, this approach is based on the theory of intrinsic motivation and social constructivism, which emphasizes the importance of active, collaborative, and meaningful learning experiences. The results of the evaluation showed a significant increase in the enthusiasm of teachers and children during the teaching-learning process, reflected in the high participation, increased concentration, and positive response to the methods applied. Thus, gamification has proven to be effective as a transformational strategy in Sunday School teaching and can be a contextual, fun, and educational approach based on Christian spiritual values and love.